Adenovirus, herpes simplex virus and cytomegalovirus infection in a lung transplant recipient. (2018) - Nagarakanti, Sandhya; Bishburg, Eliahu; Bapat, Anita
Abstract: Allograft infections post lung transplantation have a significant impact on morbidity and mortality. We report a rare case of triple viral infection with adenovirus, Herpes Simplex virus (HSV) and Cytomegalovirus (CMV) in a lung transplant recipient.